Optimal treatment sequence in COPD: Can a consensus be found? - Ferreira, J (2016)
There is currently no consensus on the treatment sequence in chronic obstructive pulmonary disease (COPD), although it is recognized that early diagnosis is of paramount importance to start treatment in the early stages of the disease. Although it is fairly consensual that initial treatment should be with an inhaled short-acting beta agonist, a short-acting muscarinic antagonist, a long-acting beta-agonist or a long-acting muscarinic antagonist. As the disease progresses, several therapeutic options are available, and which to choose at each disease stage remains controversial. When and in which patients to use dual bronchodilation? When to use inhaled corticosteroids? And triple therapy? Are the existing non-inhaled therapies, such as mucolytic agents, antibiotics, phosphodiesterase-4 inhibitors, methylxanthines and immunostimulating agents, useful? If so, which patients would benefit? Should co-morbidities be taken into account when choosing COPD therapy for a patient? This paper reviews current guidelines and available evidence and proposes a therapeutic scheme for COPD patients. We also propose a treatment algorithm in the hope that it will help physicians to decide the best approach for their patients. The authors conclude that, at present, a full consensus on optimal treatment sequence in COPD cannot be found, mainly due to disease heterogeneity and lack of biomarkers to guide treatment. For the time being, and although some therapeutic approaches are consensual, treatment of COPD should be patient-oriented.